CLASH OF EXPECTATIONS IN NAYANTARA SAHGAL'S 'A TIME TO BE HAPPY' - Trivedi, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In modern time majority of the problem of husband-wife relationship relate to career-consciousness, status and self esteem. It is quite understandable that when a man and woman marry they bring with them differences of habits, attitudes and beliefs which necessitate compromises. Where adaptability fails or is too slow to cope with the demands of the situation, the consequence is discord in married life. As such it is expected of husband and wife that they should understand human nature and human relationships. It all depends on whether the couples recognise their needs, accord importance to each other within the ambit of their dealing or not. Conflict of personalities arises when they fail to achieve an agreement on common needs and wishes, or come to disregard the sense of confidence in each other.